Passively Q-switched erbium-doped fiber laser based on two-dimensional boron carbide nanoparticles as saturable absorber - Jasem, Iman N.; Abdullah, Hiba H.; Abdulrazzaq, Mohammed J. (Optical and quantum electronics, 2024)
The utilization of boron carbide nanoparticles (B 4 C) as a saturable absorber (SA) for generating pulses by a fiber laser operating in Q-switched mode is the subject of our investigation, the findings of which are presented. This was accomplished by combining boron carbide nanoparticles (B 4 C-NPs) with polyvinyl alcohol (PVA) to form a thin-film-based SA. This SA was then placed within an erbium-doped fiber laser (EDFL) in a ring cavity configuration to enable passive Q-switching operation. The modulation depth of the B 4 C-SA was 2.3%. Stable Q-switching laser operation was accomplished with a pump power of 180 mW and central wavelength of 1561 nm by producing laser pulses with a pulse duration of 15.27 µs and pulse repetition rate of 31.6 kHz. A comparable pulse energy, which was attained at the maximum pump power of 275 mW, was approximately 2.61 nJ. The radio-frequency spectrum was examined to verify the pulse stability. The study showed a signal-to-noise ratio of 35 dB. These results expand the potential of B 4 C-based saturable absorbers, making them strong contenders for innovative photonic devices.